Neutrophil Phagocytosis of Platelets in the Early Phase of 2,4,6-trinitro-1-chlorobenzene (TNCB)-induced Dermatitis in Mice - Daito, Junko (JAPAN SOCIETY OF HISTOCHEMISTRY AND CYTOCHEMISTRY, 2014)
Activated platelets form platelet–leukocyte aggregates in the circulation in inflammatory diseases. We investigated whether activated platelets in inflamed skin tissues are phagocytized and removed by neutrophils. To investigate the kinetics of platelets and neutrophils, we immunohistochemically examined the spatiotemporal distribution of them in a murine model of 2,4,6-trinitro-1-chlorobenzene (TNCB)-induced dermatitis by using confocal and structured illumination microscopy. Four hours after elicitation, aggregates of CD41-positive platelets were adhered to CD31-positive endothelial cells within the vessels, and CD62P and PF4, markers of activated platelets, were expressed on platelet aggregates. At 8 hour post-elicitation, fragmented CD41-positive platelets were located both inside and outside vessels. Twenty-four hours after elicitation, the number of Ly-6G-positive neutrophils ingesting fragmented CD41-positive platelets outside vessels was increased, and CD62P and PF4 expression on the phagocytosed platelets was no longer observed. Disc-shaped CD41-positive platelets were not found outside vessels at any time during the experiment. Our data revealed that aggregates of activated platelets inside vessels were ingested and removed by neutrophils in the early stage of TNCB-induced dermatitis, suggesting that the process of removal of activated platelets by neutrophils may play an important role not only in the early phase of skin inflammation but also in other types of acute inflammation.